Examination of the nutritional intake of patients undergoing opioid replacement therapy: A systematic review. Issue 1 (19th December 2022) - Waddington, Freya; Naunton, Mark; Thomas, Jackson; Kyle, Greg; Wheatley, Brendon; Oguoma, Victor
Abstract: Aim: This systematic review aimed to determine the level of existing research that investigates the intake, specifically macro and micronutrient intake, of patients undergoing opioid replacement therapy. Methods: A systematic review was conducted across PubMed, Embase, Cochrane and CINAHL databases using a pre‐determined protocol. Studies published between 2001 and 2022 assessing macronutrient or micronutrient intake in opioid replacement therapy patients were included. The Strengthening the Reporting of Observational Studies in Epidemiology checklist was utilised for quality appraisal. Data from each of the included papers was synthesised in a narrative manner. Data extracted included all measurements of nutrition including macronutrient, and micronutrient intake and any bioanalysis results and methods utilised. Results: Seven papers (one cohort study and six cross‐sectional studies, n = 443) were included that investigated an aspect of nutritional intake in patients receiving opioid replacement therapy. The majority of included papers reported an assessment of both macro and micronutrient and resulting energy intake as determined by food consumption. The included papers described a picture of irregular nutritional intake in patients undergoing opioid replacement therapy. Conclusion: Minimal research into the nutritional intake of opioid replacement therapy patients exists. The existing research is suggestive of irregular nutritional intake from both macro and micronutrient consumption and indicates a need for further studies and increased attention on this vulnerable patient group.